Aransemen Lg. Rangkaian Melati Karya R. Maladi Sebagai Materi Musikal Minus One Instrumen Keroncong - Mei Artanto (Institut Seni Indonesia Denpasar, 2022)
The musical arrangement is a process of developing and setting the musical aspects of existing songs, namely Lg. Rangkaian Melati by R. Maladi became a way to improve musical material in minus one intrusion keroncong. Efforts to improve musical material minus one through musical arrangements at the same time want to question: 1) what musical aspects become exploratory material in arrangements and 2) how the arrangement process is carried out. The goal is to find out the technical procedures of musical processing arrangements Lg. Rangkaian Melati by R. Maladi for seven keroncong instruments and find out what musical aspects have the opportunity to be explored more deeply to present a musical experience that varies in minus one keroncong instrument. Qualitative research methods and Practice-Based Research (PBR) are used in this article as investigative procedures in uncovering aspects of knowledge of the practice process and the results of the Arrangement of Lg. Rangkaian Melati for keroncong instruments. The results of the analysis found in this article are 1) two musical aspects can be used as exploratory material in the arrangement of Lg. Rangkaian Melati, namely harmony (chord movement) and melody (for auxiliary members and fillers), and 2) the process of exploration of musical aspects and arrangement work can be done systematically and structured through a five-step method of musical arrangements accompanied by systematic musicology perspective.